Mythological Codes in Turkic Heroic Epics: A Comparative Typological Analysis of Alpamish, Manas, And Köroğlu - Olima Abdivaliyevna Xolmurodova (International Journal Of Literature And Languages, 2026)
This study presents a systematic comparative-typological analysis of mythological codes embedded in five major Turkic heroic epics — Alpamish (Uzbek), Alpamys Batyr (Kazakh), Manas (Kyrgyz), Köroğlu (Turkmen/Azerbaijani), and Oghuz-Name (Uyghur). Drawing on Lévi-Strauss's concept of mythological codes, Jung's archetypal theory, and Campbell's monomyth framework, the research identifies five recurring mythological codes: (1) divine birth and celestial mandate (Tengri), (2) the sacred horse as cosmic mediator, (3) the tripartite world structure (upper–middle–lower), (4) the underworld captivity-and-return motif, and (5) the demonological antagonist (Albasti, Dev, shape-shifters). Textual analysis of primary epic sources combined with a comparative structural method reveals that these codes operate as deep semiotic structures that transcend individual ethnic boundaries while simultaneously encoding distinct cultural identities. The findings contribute to ongoing debates in Turkic.